Resolution on the Recognition of Material Evidence as a Criminal Procedural Decision - Hetman, Halyna (Problems of legality, 2026)
The article is devoted to the study of certain issues of such criminal procedural decisions of investigators, detectives, inquiry officers and prosecutors as rulings on the recognition of objects that were the subject of a criminal offence (or contain traces thereof) as material evidence at the stage of pre-trial investigation. The paper analyses the current criminal procedural legislation in comparison with certain provisions of the 1960 Criminal Procedure Act and considers contemporary approaches to understanding such a criminal procedural decision as a ruling by the prosecution. It has been determined that a ruling is a criminal procedural decision made by an investigator, detective, inquiry officer, or prosecutor, which is documented on an official form, in which, through a brief summary of the facts available in the criminal proceedings, a conclusion is formulated regarding the need to carry out the actions provided for by criminal procedural law or, conversely, formulates a statement prohibiting their implementation on the basis of justification and within the limits of procedural law, which, in turn, gives rise to certain procedural links or facts, with the help of which the authorised subjects of the prosecution can obtain new factual circumstances, verify or refute those previously obtained. When considering the necessity of adopting this criminal procedural decision at the stage of pre-trial investigation in criminal proceedings as a ruling on the recognition of material evidence, scientific approaches were analysed and it was determined that there are two schools of thought on this issue, one of which is that it is necessary for representatives of the prosecution to draft such a ruling, while the other argues that the drafting of such a decision is unnecessary and does not meet the requirements of modern criminal procedural law. In addition, the study of the need to adopt a resolution on the recognition of material evidence is also based on an analysis of the current practice of national courts, in particular, individual rulings of investigating judges have been studied and a judicial approach has been identified that recognises the need for such a procedural document as a resolution on the recognition of material evidence when deciding on the seizure of property and the removal of the seizure from property. An analysis of ECHR decisions has also been carried out, which have developed specific standards for the appropriateness, admissibility and reliability of seizing property from individuals during pre-trial investigations.